Enhancing Language Learning through Literary Integration: A Pathway to Twenty-First-Century Proficiency - Holbah, Wael Ali; Sharma, Vipin Kumar; Hamdi, Sami Abdullah; Habiburrahim, Habiburrahim (Jurnal Ilmiah Peuradeun, 2025)
In the rapidly evolving landscape of global education, English as a Second or Foreign Language (ESL/ EFL) pedagogy faces persistent challenges such as declining learner engagement, test-driven instruction, and insufficient development of intercultural competence. Literature, despite its proven capacity to foster linguistic proficiency, critical thinking, and cultural sensitivity, has remained underutilized and inconsistently applied in language classrooms. This study sought to reposition literature as a central element in ESL/ EFL education by examining how it can be systematically integrated into pedagogy. Employing a qualitative content analysis of thirty peer-reviewed articles published between 2000 and 2025, the study synthesized recurring themes across diverse contexts using NVivo-supported coding and thematic analysis. Five key themes emerged: pedagogical effectiveness, learner engagement, cultural relevance, cognitive development, and critical thinking integration. Building on these findings, the study introduced the Literary Integration Pedagogical Framework (LIPF), a model that unifies sociocultural scaffolding, emotional engagement, and critical literacy into a coherent and adaptable approach. The LIPF contributed theoretically by bridging previously fragmented perspectives and practically by offering curriculum designers, educators, and policymakers an evidence-based strategy for revitalizing language teaching. This study demonstrates that literature is not a peripheral supplement but an indispensable resource for cultivating linguistically competent, emotionally intelligent, and critically aware global citizens.